Essence and purpose of preventive and punitive functions of legal liability - V. Tymoshenko (Юридичний часопис Національної академії внутрішніх справ)
The relevance of this general theoretical study is conditioned by the growing number of offences in the country, which indicates problems in society and the state, including the insufficient effectiveness of legal liability, and the need to improve its regulatory framework and proper performance of functions. The study analysed the preventive and punitive functions of legal liability as essential factors of prevention of unlawful behaviour. The purpose of this study was to initiate a scientific discussion on the mechanisms of legal liability’s impact on unlawful behaviour, and to determine the possibilities of preventive and punitive functions in terms of preventing unlawful behaviour. The methodological framework of the study was based on formal-logical, systemic, and structural-functional methods employed within the framework of dialectical, phenomenological, and systemic approaches. The study resulted in the hypothesis that the normative model of legal liability (in the objective sense) can only serve as a general prevention of offences. The existence of a legal fact of an offence leads to legal liability in the subjective sense. At this stage, the punitive function is fully realised. Only the interaction of these functions will contribute to the implementation of the tasks of the institution of legal liability, primarily the prevention of offences. Thus, the functions of legal liability are its impact, practical implementation of the purpose which is expressed in establishing the legal limits of a person’s conduct by means of its incentives, coercion, or punishment; the key functions are preventive and punitive; the preventive function is aimed at prevention and deterrence of offences, which is achieved by establishing sanctions for their commission; the punitive function covers both the purpose of punishment and education, and is implemented at the individual level by force in a certain procedural form. The practical significance of this study is that law enforcement agencies can use the findings to formulate effective strategies for developing modern political- legal instruments for preventing unlawful behaviour